MYLK*FLNB and DOCK1*LAMA2 gene–gene interactions associated with rheumatoid arthritis in the focal adhesion pathway - Veyssiere, Maëva; Rodriguez Ordonez, Maria del Pilar; Chalabi, Smahane; Michou, Laetitia; Cornelis, François; Boland, Anne; Olaso, Robert; Deleuze, Jean-François; Petit-Teixeira, Elisabeth; Chaudru, Valérie (Frontiers in Genetics, 2024)
Rheumatoid arthritis (RA) is a chronic, systemic autoimmune disease caused by a combination of genetic and environmental factors. Rare variants with low predicted effects in genes participating in the same biological function might be involved in developing complex diseases such as RA. From whole-exome sequencing data, we identified genes containing rare non-neutral variants with complete penetrance and no phenocopy in at least one of 9 French multiplex families.Further enrichment analysis highlighted focal adhesion as the most significant pathway. We then tested if interactions between the genes participating in this function would increase or decrease the risk of developing RA disease. The MB-MDR (Model-Based Multifactor Dimensionality Reduction) approach was used to detect epistasis in a discovery sample (19 RA cases and 11 healthy individuals from 9 families and 98 unrelated CEU controls from the International Genome Sample Resource). We identified 9 significant interactions involving 11 genes (MYLK, FLNB, DOCK1, LAMA2, RELN, PIP5K1C, TNC, PRKCA, VEGFB, ITGB5, FLT1). One interaction (MYLK*FLNB) increasing RA risk and one interaction decreasing RA risk (DOCK1*LAMA2) were confirmed in a replication sample (200 unrelated RA cases and 91 GBR unrelated controls). Functional and genomic data in RA samples or relevant cell types argue the key role of these genes in RA.